Modellbasierte Entscheidungsunterstützung für Vertraulichkeit und Datenschutz in Geschäftsprozessen - Alpers, Sascha (KIT Scientific Publishing, 2023)
Information Confidentiality and Data Protection Networks (ICPN) support process modelers and process managers in not only taking a purely technical view of data protection and confidentiality, but also in taking it into account at an early stage in the design of business processes. The Petri-net extension ICN published in the book makes it possible to systematically consider confidentiality and data protection aspects within business process models.